Hubungan Tingkat Kecukupan Zat Besi, Asam Folat, dan Vitamin B12 dengan Anemia Remaja Putri - Novia Sari Aulia; Desti Ambar Wati; Lara Ayu Lestari; Abdullah (JURNAL RISET GIZI, 2025)
Background: Anemia happens when the body has too few red blood cells or low hemoglobin. It usually comes from not having enough iron. Not getting enough folic acid can also cause anemia because folic acid and vitamin B12 help make healthy red blood cells. Globally, the WHO identifies adolescent girls as a group at high risk of anemia, with prevalence rates in developing countries reported to range from 40–88%, and some studies suggest figures as high as 50–60% depending on regional conditions. In Indonesia, the 2023 Indonesian Child Health Survey (SKI) recorded an anemia prevalence of 15.5–18% among adolescents aged 15–24, although some regions still show much higher rates, reaching 40–50%. This data confirms that anemia in adolescent girls remains a priority health issue related to micronutrient adequacy. Objective: This research seeks to examine the association between the adequacy of iron, folic acid, and vitamin B12 intake and the occurrence of anemia in adolescent girls within the Rama Indra Community Health Center service area in 2024. Method: This research employed a quantitative method with a cross-sectional design. The sample included 80 adolescent girls, selected through stratified random sampling. The research was conducted from October 14 to December 17, 2024, at the selected schools. Data were collected through interviews using the SQ-FFQ to evaluate the adequacy of iron, folic acid, and vitamin B12 intake, while hemoglobin levels were measured using the Easytouch GCHb device. Kendall’s Tau-c test in SPSS was used to analyze correlations. Results: Most participants exhibited poor nutritional status, with deficiencies observed in iron (71.25%), folate (67.5%), and vitamin B12 (48,8%). Bivariate analysis revealed significant correlations between anemia and the adequacy of iron (p=0.000), folate (p=0.006), and vitamin B12 (p=0.024). Conclusion: A significant relationship exists between the adequacy of iron, folic acid, and vitamin B12 and the occurrence of anemia among adolescent girls in the Rama Indra Health Center’s service area.